European integration and income inequality - Jason Beckfield (Luxembourg Income Study (LIS), 2006)
Globalization has attained a prominent place on the sociological agenda, and stratification scholars have implicated globalization in the increased income inequality observed in many advanced capitalist countries. But sociologists have given much less attention to a different but increasingly prevalent form of internationalization: regional integration. Regional integration, or the construction of international economy and polity within negotiated regions, should matter for income inequality. Regional economic integration should raise income inequality, as workers are exposed to international competition and labor unions are weakened. Regional political integration should also raise income inequality, but through a different mechanism: where the regional polity advances market-oriented policies, political integration should drive welfare state retrenchment as states adopt liberal policies in a context of fiscal austerity. Evidence from random-effects and fixed-effects models of national income inequality in Western Europe supports these arguments. The significant effects of regional integration on income inequality are net of several controls, including two established measures of globalization, suggesting that a sociology of regional integration adds to our understanding of rising income inequality in Western Europe.
Keywords: 330; Europäische Integration; Verteilungsgerechtigkeit; Eurozone; Schätzung; EU-Staaten